Art Workshop as A Form of Participatory Activity and Stimulation of Community Creativity - Novia Nur Kartikasari; Rahma Khairunnisa (Nusantara Science and Technology Proceedings, 2023)
Creative potential is formed from experience, also influenced by various factors in the surrounding environment. Community service actions, especially in the arts, also play a role in influencing the creative process of a person or group of people. Community service is identical to activities in the form of workshops as a stimulation of the community's creative power, providing new experiences, and often as a means of entertainment. Creative activities maximally supported from various sides can maximize the work created. This paper aims to map the various things that influence creativity in human art, especially in art workshops, where people participate with creative awareness, and how these stages take place. The method used is descriptive qualitative with a relational aesthetic approach, that the work is not only understood as the creation of one person but also the relationship between the artist and the audience. In the workshop, the community acts as an audience that is also involved or participatory activities. The result of this study is a description of the various things that influence the creative process in the community, especially in workshop activities, as well as how the creative process is formed, related to the different characters of each workshop participant and also the abience that has been built in the workshop location environment.